2017
DOI: 10.1038/s41598-017-02486-6
|View full text |Cite
|
Sign up to set email alerts
|

Recalcitrant carbon components in glomalin-related soil protein facilitate soil organic carbon preservation in tropical forests

Abstract: Glomalin-related soil protein (GRSP) is known as an important microbial by-product which is crucial for preserving or accumulating soil organic carbon (SOC). However, the underlying mechanisms are not well understood. In this study, we investigated the chemical structures of GRSP and its relationship with SOC using 13C nuclear magnetic resonance (NMR) in three tropical forests. The three forests, including a planted forest (PF), a secondary forest (MF) and a primary forest (BF), were selected to represent the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 62 publications
(88 reference statements)
4
43
0
Order By: Relevance
“…In contrast, broadleaved forest was considered to N‐saturated and phosphorus‐limited (Fang et al, ; Huang et al, ; Lu et al, ), and soil respiration of the broadleaved forest was less sensitive than the coniferous forest or the mixed forest to the high N deposition (Deng et al, ). Finally, the composition of microbial community was observed to be significantly different between the pines dominated coniferous forest and broadleaf dominated mixed forest or broadleaved forest, with arbuscular mycorrhizal fungi being dominant in the broadleaved forest and nonarbuscular mycorrhizal fungi in the coniferous forest (Liao et al, ; Zhang et al, ). This difference in microbial composition can also influence SOC stabilization through microbial by‐product, such as glomalin‐related soil protein, as shown in the soil sampled taken from three forests by Zhang et al ().…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, broadleaved forest was considered to N‐saturated and phosphorus‐limited (Fang et al, ; Huang et al, ; Lu et al, ), and soil respiration of the broadleaved forest was less sensitive than the coniferous forest or the mixed forest to the high N deposition (Deng et al, ). Finally, the composition of microbial community was observed to be significantly different between the pines dominated coniferous forest and broadleaf dominated mixed forest or broadleaved forest, with arbuscular mycorrhizal fungi being dominant in the broadleaved forest and nonarbuscular mycorrhizal fungi in the coniferous forest (Liao et al, ; Zhang et al, ). This difference in microbial composition can also influence SOC stabilization through microbial by‐product, such as glomalin‐related soil protein, as shown in the soil sampled taken from three forests by Zhang et al ().…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the composition of microbial community was observed to be significantly different between the pines dominated coniferous forest and broadleaf dominated mixed forest or broadleaved forest, with arbuscular mycorrhizal fungi being dominant in the broadleaved forest and nonarbuscular mycorrhizal fungi in the coniferous forest (Liao et al, 2018;Zhang et al, 2017). This difference in microbial composition can also influence SOC stabilization through microbial byproduct, such as glomalin-related soil protein, as shown in the soil sampled taken from three forests by Zhang et al (2017). As a result of the significant leaching process in fine-textured soils along vertical profile, SOC was often found to be negatively correlated with soil clay content, as SOC was typically high in soil surface and clay content was high in illuvial B horizons.…”
Section: 1029/2018jg004995mentioning
confidence: 98%
“…The soil selected for optimization came from typical middle European arable regions and it contained glomalin in an amount 2.41 mg/g. For instance, level glomalin in soil from China was reported to be 3.94 mg/ml . The low limit of detection gives opportunity to analyze even soils with low fertility.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, GRSP has a positive contribution to the soil C pools in native grasslands for a soil binding agent (Purin et al 2006). Combined with three kinds of soil samples obtained from the surface soil to the depth of 20 cm, Zhang et al (2017a) drew a linear correlation between GRSP and SOC. It is estimated that GRSP accounts for 4% to 5% of total soil C source, which was higher than the contribution of microbial biomass C in Hawaiian soils (Wu et al 2014b).…”
Section: Grsp Functioning On Soil Organic Carbonmentioning
confidence: 99%
“…It seems that GRSP may not provide a positive contribution to the SOC pool. Recently, the chemical structure of GRSP was shown by the method of the solid-state 13 C cross polarisation magic angle spinning (Zhang et al 2017a). The result showed that GRSP had a high carboxyl C ratio (40% of total content) and relatively high aromatic hydrocarbon ratio (30% of total content) and alkyl C (20% of total content).…”
Section: Grsp Functioning On Soil Organic Carbonmentioning
confidence: 99%